Preparation and characterization of dialdehyde β-cyclodextrin with broad-spectrum antibacterial activity. (September 2018) - Ren, He; Lyu, Yongbo; Li, Xinying; Zhang, Shuxiao; Ye, Yusong; Li, Defu; Mu, Changdao
Abstract: Consumers demand more alternatives of riskless antibacterial agents to prevent microbial contamination in food industry. Oxidized carbohydrate may be a potential option as new antibacterial agent. However, the relatively weak antibacterial property of oxidized carbohydrate is not satisfactory. In this paper, dialdehyde β-cyclodextrins with different oxidation degree were prepared by periodate oxidation and their antibacterial properties were systematically studied. The results showed that multi-aldehyde groups were successfully introduced into β-cyclodextrin molecules by periodate oxidation. The aqueous solubility and stability of dialdehyde β-cyclodextrins were improved as expected. It is interesting that dialdehyde β-cyclodextrins possessed outstanding antibacterial activity against both Gram-positive and Gram-negative bacteria. The minimal inhibitory concentrations against E. coli, S. aureus and B. subtilis reached 0.63, 1.25 and 0.63 mg/mL, respectively. Moreover, dialdehyde β-cyclodextrins effectively inhibited bacterial growth on the surface of apples. The results demonstrated that oxidized oligosaccharide with multi-aldehyde groups and good dispersibility in aqueous solution possessed satisfactory antibacterial activity, which can be used as new antibacterial agent in food industry. Graphical abstract: Unlabelled Image Highlights: Dialdehyde β-cyclodextrins with different oxidation degree were synthesized. Aqueous dispersibility of β-cyclodextrin was highly improved by oxidation. Dialdehyde β-cyclodextrin possessed outstanding antibacterial activity. Dialdehyde β-cyclodextrin could effectively extend the storage time of apple. Dialdehyde β-cyclodextrin could be used as new antibacterial agent in food industry.